PENGARUH LIVE STREAMING, HEDONIC SHOPPING MOTIVATION, PRICE DISCOUNT, DAN ONLINE CUSTOMER REVIEW TERHADAP IMPULSE BUYING E-COMMERCE SHOPEE - Mirza Elysia, Tia Sonia; Bara Zaretta; Herry Subagyo; Suhita Whini Setyahuni (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
Indonesia dominates global e-commerce with Shopee as the leading platform, reaching 21.56% penetration in 2023 and a projected growth of 34.84% in 2029. This study analyzes how live streaming, hedonic shopping motivation, price discount, and online customer review factors contribute to impulse buying behavior on the Shopee platform. This quantitative research involved 102 university students in Semarang who had a history of at least one e-commerce transaction in the past month, selected using purposive sampling method. Data was collected through an online questionnaire in December 2024 and analyzed with multiple linear regression using IBM SPSS. The results showed that the variables of live streaming, hedonic shopping motivation, and price discount had a significant positive effect on impulse buying, while the online customer review variable had no significant effect on impulse buying. Regression analysis indicates that the R-square value of 92.2% of impulse buying variables can be explained by the independent variables studied, with the remaining 9.8% influenced by external factors outside the research model. Shopee needs to strengthen the live streaming feature and the hedonic shopping aspect through dynamic displays and special discounts for students. Future research should expand coverage to several e-commerce platforms and add ease of payment variables.